Trauma terhadap Kekerasan dan Kehilangan sebagai Pemicu Gangguan Jiwa : Kajian Psikososial di Rumah Sakit Jiwa Prof. Dr. M Iidrem - Cindri Madelta; Rahayu Fuji Astuti; Desy Kartka Dewi; Risqi Aulia Syahfitri; Sintia Agustina (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the various forms of trauma experienced by patients with mental disorders, particularly those caused by violence and loss, and explores the psychosocial approaches used in the recovery process at Prof. Dr. M. Ildrem Mental Hospital, Medan. The background of this study is based on the importance of understanding traumatic factors as one of the root causes of mental disorders, which are often overlooked in medical treatment. The research aims to describe the types of trauma experienced by patients and to evaluate the effectiveness of the psychosocial interventions provided by the hospital. A qualitative approach was employed, using field observation and in-depth interviews with rehabilitation staff, including psychologists, counselors, and therapists. The findings indicate that the majority of patients have a history of severe trauma, such as sexual violence, the loss of loved ones, and extreme life stress that was not properly addressed. The recovery process at the hospital is carried out holistically through occupational therapy, skills training, spiritual guidance, and psychological support from both professionals and peer counselors. The study concludes that an approach combining scientific methods with patients' real-life experiences can positively impact the recovery process. Therefore, strengthening professional capacity and providing counselor training are essential to enhance the effectiveness of the rehabilitation system.